(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت الدراسة إلى التعرف إلى أسباب الانتكاس والعودة إلى تعاطي المخدرات بعد العلاج. والـتعرف إلى الفروق في أسباب الانتكاس والعودة إلى التعاطي بحسب المادة المخدرة وبحسب المستوى التعليمي. وقد تم إعداد استبيان يتكون من أربعة أقسام. يضم القسم الأول البيانات الشخصية، والقسم الثاني معلومات عن المستوى الاقتصادي الاجتماعي، القسم الثالث معلومات حول الإدمان، القسم الرابع معلومات عن الانتكاس. وتكونت عينة البحث من 145 مدمناً منتكساً من المرصد الوطني لرعاية الشباب. أهم النتائج: • · غالبية أفراد العينة قد انتكست وعادت للتعاطي أكثر من مرة. • · أهم أسباب الانتكاس والعودة للتعاطي فهي: "عدم القدرة على واجهة المشكلات والضغوط"، ثم "ظهور مشكلات نفسية (القلق والاكتئاب)"، و"العودة للاختلاط مع المدمنين.."، و" المشكلات الأسرية " • لا يوجد فرق ذو دلالة إحصائية في أسباب الانتكاس لدى عينة البحث بحسب متغير المستوى التعليمي، ولا بحسب نوع المادة المتعاطاة ماعدا مادة الكحول والهيروين. This study aimed at identifying the reasons for relapsing into using drugs, identifying the differences in the reasons for relapse and addiction in terms of the narcotic substance used or the educational level variable. A questionnaire divided into 4 sections is prepared. The first section contains personal data; the second contains information about the socio-economic level; the third section contains information on addiction; and the fourth contains information about relapsing. The research sample contains 145 relapsed addicts of the National Center of Youth Care. The most important results obtained are as follows: • · The majority of the sample individuals have relapsed more than one time. • · The important reasons for relapsing and going back to using drugs are: -Incapability of facing troubles and pressures. -Emergence of psychological problems (depression and anxiety). -Family problems. -Going back to mixing with addicts. • · Statistically, the research sample displays no significant differences in the reasons for relapsing in terms of the educational level variable or the narcotic substance used except for alcohol and heroine.